The Clinical Characteristics and Prognosis Factors of Mild-Moderate Patients With COVID-19 in a Mobile Cabin Hospital: A Retrospective, Single-Center Study - Zhang, Jishou; Wang, Menglong; Zhao, Mengmeng; Guo, Shanshan; Xu, Yao; Ye, Jing; Ding, Wen; Wang, Zhen; Ye, Di; Pan, Wei; Liu, Menglin; Li, Dan; et al. (Frontiers in Public Health, 2020)
Background: Novel mobile cabin hospitals have been built to provide more makeshift beds for patients with COVID-19 in Wuhan. However, the value of the temporary hospital and characteristics of these patients needed be further described. Methods: This was a retrospective, single-center study. A total of 869 patients with confirmed COVID-19 were admitted to Wuchang Mobile Cabin Hospital in Wuhan, between February 6th, 2020 and February 20th, 2020. The final date of follow-up was March 6th, 2020. Clinical characteristics and outcome data were collected and analyzed. Results: Of 869 patients, the median age was 51 years (IQR, 40-58 years), and 43.4% patients were men. A total of 616 patients (70.9%) were discharged, 95 patients (10.9%) were transferred to the designated hospital due to worsening condition (endpoint), and 158 patients (18.2%) were still in the hospital. The incidence of the main symptoms, including fever, cough, fatigue, muscle aches and anorexia, decreased with time. However, there were no differences in outcome among the patients with different onset times. Generally, both patients aged 45 years or older and patients with comorbidities were more likely to reach the endpoint (condition worsen). Conclusion: Novel mobile cabin hospitals were recommended to serve mild/moderate patients with COVID-19 and were a practical intervention to improve the region's medical affordability. Older age and comorbidity were associated with poor prognosis (condition worsen) for mild-moderate patients. The initial symptoms of mild-moderate patients gradually became insidious, which deserves our attention.